Robert Jenson’s ecumenical vision based on his Trinitarian thought - Verhoef, AH (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
The American Lutheran theologian, Robert Jenson, is well known as an ecumenical theologian. He is also well known as a significant and prolific writer of Trinitarian theology during the last forty years. These two themes, Ecumenism and Trinity, are very closely interconnected in Jenson’s life and work. We can say that his Trinitarian theology has been his leitmotiv and inspiration for his life-long ecumenical engagement, and vice versa, that his ecumenical vision and dedication has influenced and motivated his Trinitarian theology in many ways. In this paper I will explore the ecumenical perspectives and proposals Jenson has made as logical implications of his Trinitarian theology. I will argue that his understanding of the relationship between the Trinity and time helped to form his ecumenical vision and contributed to some of his ecumenical proposals. This will give an indication of how Jenson is searching for a theology of the one church of the future.